Dynamic properties of inhomogeneous states in cuprates: General Aspects - Lorenzana, J.; Seibold, G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
We review the static and dynamical properties of stripe textures with regard to their relevance in high-Tc superconductors. Our investigations are based on the time-dependent Gutzwiller approximation which allows for the computation of random-phase approximation-like (RPA) fluctuations on top of the Gutzwiller approximation (GA). No restrictions are imposed on the charge and spin configurations which makes the method suitable for the calculation of linear excitationsaround symmetry-broken solutions. Within this approach we calculate the optical conductivity of stripes and compare our results with reflectivity experiments on cuprates. Furtheron we use the spin-rotational invariant extension of the GA + RPA method in order to investigate the characteristics of magnetic excitations in the stripe phase of cuprates. Our results are in very good agreement with neutron scattering and optical experiments on lanthanum cuprate superconductors.